Behavior of confined concrete with recycled glass fiber-reinforced polymer needles as coarse aggregates under axial compression. (15th July 2023) - Cheng, Cai-Shu; Xu, Yuan-Bin; Xiao, Cong-Yue; Fu, Bing; Gao, Ruo-Fan; Kuang, You-Di
Abstract: Cutting waste GFRP into needles as part of coarse aggregates in concrete shows to be a promising approach for recycling the waste GFRP composites. However, the resulting concrete has its compressive strength lower than that of normal concrete, and is therefore limited for use in nonstructural elements. The present study proposes a method to improve the robustness of such concrete in structural elements by utilizing the confined concrete concept, in which the concrete with GFRP needles is confined with carbon fiber-reinforced polymer wraps. A series of compression tests under concentric loading were conducted with the ratio of GFRP needles to the total coarse aggregates (i.e., replacement ratio) and the confining jacket stiffness as the two test parameters. The test results indicate that the compressive strength of unconfined concrete decreased by approximately 10% due to replacing 15% coarse aggregates with GFRP needles, while the confining jackets of the same stiffness applied resulted the compressive performance of the confined concrete with needles comparable to or even slightly higher than that of its counterpart without needles. Two widely-used theoretical models were used to predict the compressive performance of the confined concrete, finding that both of them overestimated the axial stress but underestimated the axial strain of the confined concrete with GFRP needles. Therefore, a refined model is required to predict the behavior of confined concrete with GFRP needles under axial compression. Highlights: Recycled GFRP-needles decreases the compressive strength and elastic modulus of unconfined concrete. CFRP jacketing significantly improves the performance of concrete. The replacement ratio of GFRP needles has a minor effect on the compressive behavior of confined concrete. Both theoretical models used for comparison overestimated the axial stress but underestimated the axial strain.